1992
DOI: 10.1093/carcin/13.12.2197
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic potential of tamoxifen and analogues in female Fischer F344/n rats, DBA/2 and C57BL/6 mice and in human MCL-5 cells

Abstract: Chronic administration of tamoxifen to female rats causes hepatocellular carcinomas. We have investigated damage to liver DNA caused by the administration of tamoxifen to female Fischer F344/N rats or C57B1/6 or DBA/2 mice using 32P-postlabelling. Following the administration of tamoxifen for 7 days (45 mg/kg/day) and extraction of hepatic DNA, up to 7 radiolabelled adduct spots could be detected after PEI-cellulose chromatography of the 32P-labelled DNA digests. Tamoxifen caused a time-dependent increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(135 citation statements)
references
References 0 publications
6
127
0
2
Order By: Relevance
“…Examples of other typical schedules for use of the CBMN Cyt assay for in vitro genotoxicity testing are summarized in an option when testing new chemicals 57,58,63 but this could limit the exposure period owing to the possible cytotoxicity of S9 to the target cells. A better option may be the use of metabolically competent cells such as genetically modified MCL-5 cells 98 .…”
Section: Other Primary Cell Culturesmentioning
confidence: 99%
“…Examples of other typical schedules for use of the CBMN Cyt assay for in vitro genotoxicity testing are summarized in an option when testing new chemicals 57,58,63 but this could limit the exposure period owing to the possible cytotoxicity of S9 to the target cells. A better option may be the use of metabolically competent cells such as genetically modified MCL-5 cells 98 .…”
Section: Other Primary Cell Culturesmentioning
confidence: 99%
“…The most common adverse drug reaction consists in climacteric-like symptoms, but the drug has also been reported to generate DNA adducts in human hepatocyte cultures and in rats and Syrian hamsters (Han et al, 1992;White et al, 1992;Hard et al, 1993). TAM is a liver carcinogen in rats (Hirsimaki et al, 1993;Vancutsem et al, 1994) and it increases the risk of endometrial and gastrointestinal cancers in patients (Fisher et al, 1994; De Gregorio et al, 1995;Rutqvist et al, 1995) and increases the number of polyps in the endometrium (Lahti et al, 1993).…”
mentioning
confidence: 99%
“…Nor does TOR generate DNA adducts in the rat liver (White et al, 1992;Hard et al, 1993). In a 2-year study in rats TOR was not carcinogenic (Karlsson et al, 1996).…”
mentioning
confidence: 99%
“…Tamoxifen induced a significant increase in micronucleus formation in a dose dependent manner in cultures of MCL-5 cells, a human cell line that expresses five different human cytochrome P450 isoenzymes, as well as epoxide hydrolase. Exposure of rat hepatocytes to tamoxifen in vitro, resulted in induction of unscheduled DNA synthesis, when preparations from rats which had been pretreated with tamoxifen in vivo were used (White et al 1992). Wilson et al (1995) reported that 50 lM tamoxifen decreased human lymphocyte proliferation but it did not exert a genotoxic activity.…”
Section: Genotoxicitymentioning
confidence: 99%